Shell Condition and Survival of Puget Sound Pteropods Are Impaired by Ocean Acidification Conditions - Busch, D. Shallin; Maher, Michael; Thibodeau, Patricia; McElhany, Paul (W&M ScholarWorks, 2014)
We tested whether the thecosome pteropod Limacina helicina from Puget Sound, an urbanized estuary in the northwest continental US, experiences shell dissolution and altered mortality rates when exposed to the high CO2, low aragonite saturation state (Ωa) conditions that occur in Puget Sound and the northeast Pacific Ocean. Five, week-long experiments were conducted in which we incubated pteropods collected from Puget Sound in four carbon chemistry conditions: current summer surface (∼460–500 µatm CO2, Ωa≈1.59), current deep water or surface conditions during upwelling (∼760 and ∼1600–1700 µatm CO2, Ωa≈1.17 and 0.56), and future deep water or surface conditions during upwelling (∼2800–3400 µatm CO2, Ωa≈0.28). We measured shell condition using a scoring regime of five shell characteristics that capture different aspects of shell dissolution. We characterized carbon chemistry conditions in statistical analyses with Ωa, and conducted analyses considering Ωa both as a continuous dataset and as discrete treatments. Shell dissolution increased linearly as aragonite saturation state decreased. Discrete treatment comparisons indicate that shell dissolution was greater in undersaturated treatments compared to oversaturated treatments. Survival increased linearly with aragonite saturation state, though discrete treatment comparisons indicated that survival was similar in all but the lowest saturation state treatment. These results indicate that, under starvation conditions, pteropod survival may not be greatly affected by current and expected near-future aragonite saturation state in the NE Pacific, but shell dissolution may. Given that subsurface waters in Puget Sound’s main basin are undersaturated with respect to aragonite in the winter and can be undersaturated in the summer, the condition and persistence of the species in this estuary warrants further study.